How does body symmetry influence standing balance? - Kašček Bučinel, Ana (Array, 2019)
The aim of the study was to determine whether maintaining the standing balance position is influenced by athlete’s symmetric morphological characteristics. Thirty-two healthy sports students participated in this study (age 19.8±1.4 years, body height 182.9±6.8 cm, body weight 79.1±8.1 kg). Morphological characteristics are represented with differences between the left and the right body side of: forearm girth, upper arm girth, calf girth, thigh girth, long shoulder height, lean mass of legs and lean mass of arms. The standing balance result was calculated as a result of factor scores for 9 measurements of 30 seconds (3 measurements of normal standing, 3 measurements of blind standing, and 3 measurements of deaf standing) collected from the pressure insoles system and the difference in ground reaction force between the left and the right leg. Results show that the asymmetric leg load in maintaining standing balance depends on the side differences in the thigh girth and upper arm girth. The greater difference in the thigh girth in favour of the left side resulted in bigger ground reaction force on the right leg compared to the left leg and the greater difference in the upper arm girth in favour of the left side resulted in bigger ground reaction force on the left leg. To avoid one side overload, it is essential for all sports activities to be performed bilaterally.